Prognostic analysis of adjuvant chemotherapy in patients with nasopharyngeal carcinoma. (October 2013) - Lin, Ching-Chan; Chen, Tzu-Ting; Lin, Chen-Yuan; Hsieh, Ching-Yun; Lin, Po-Han; Chien, Chun-Ru; Chiu, Chang-Fang; Yeh, Su-Peng
Background: Concurrent chemoradiation has become the standard of treatment in locally advanced nasopharyngeal carcinoma. However, the exact magnitude of the benefits of adjuvant chemotherapy is still unclear.Materials & methods: This is a retrospective assessment of 181 patients with newly diagnosed, locally advanced nasopharygeal carcinoma who received concurrent chemoradiation followed by adjuvant chemotherapy with cisplatin plus fluorouracil in one institution between 2004 and 2010.Results: The median follow-up period was 40 months (range: 2.1–96.6 months). The estimated 5-year survival rate of patients with and without adjuvant chemotherapy were 83.6 and 66.7%, respectively (p = 0.027). Patients receiving two to three cycles of adjuvant chemotherapy had improved outcomes compared with those without adjuvant chemotherapy or who had received one cycle. Multivariate analysis showed that both advanced stage and suboptimal treatment of adjuvant chemotherapy were adverse risk factors in terms of overall survival and disease-specific survival.Conclusion: Adjuvant chemotherapy with two to three cycles of cisplatin plus fluorouracil improved the survival of nasopharyngeal carcinoma patients.